2018
DOI: 10.1186/s13717-018-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of diversity, stand structure and regeneration of woody species through area exclosure: the case of a mopane woodland in northern Botswana

Abstract: This study examines the effect of closed area on woody species regeneration by comparing the woody species regeneration among closure, open woodland, and degraded land areas in Loma Bosa district, Dawuro zone in southern Ethiopia. Results show that Simpson's Diversity Index was 7.24 for woody species in closed area, 6.01 in open woodland and 3.40 in open degraded land area. Shannon-Weiner Diversity Index(H') was 2.26 for woody species in closed area, 2.38 in open woodland area and 1.56 in open degraded land ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 52 publications
(55 reference statements)
10
31
1
Order By: Relevance
“…The result revealed that the five studied forests contain different tree species, which fulfill critical ecological, e.g., provision of habitats for other plants and wild animals, as well as economic functions. The species composition recorded in the studied forests was comparable to those of another dry Afromontane forest of Ethiopia (36 species) (Girma and Mosandl 2012) and a mopane woodland in northern Botswana (35 species) (Teketay et al 2018). However, it was lower than tropical forests (55 species) of Kenya (Mutiso et al 2015).…”
Section: Species Composition and Stand Structuressupporting
confidence: 72%
“…The result revealed that the five studied forests contain different tree species, which fulfill critical ecological, e.g., provision of habitats for other plants and wild animals, as well as economic functions. The species composition recorded in the studied forests was comparable to those of another dry Afromontane forest of Ethiopia (36 species) (Girma and Mosandl 2012) and a mopane woodland in northern Botswana (35 species) (Teketay et al 2018). However, it was lower than tropical forests (55 species) of Kenya (Mutiso et al 2015).…”
Section: Species Composition and Stand Structuressupporting
confidence: 72%
“…When all the species (woody species and herbaceous species) are considered, the species composition in MNR is lower than those reported from Ethiopia (Senbeta and Teketay, 2003;Zegeye et al, 2006). The diversity and evenness values of the woody species in MNR (1.44 an 0.38, respectively) are much lower than those reported for Shorobe (2.18 and 0.6, respectively), Maun (area exclosure in Island Safari Lodge, 2.15 and 0.6, respectively), Xobe (1.5 and 0.5, respectively) villages (Neelo et al, 2013;Neelo et al, 2015) as well as in an area exclosure of more than 10 years (3.14 and 1.6, respectively) in Maun (Teketay et al, 2016), northern Botswana, and other dry land forests (Senbeta and Teketay, 2003;Alelign et al, 2007;Zegeye et al, 2006).…”
Section: Discussionmentioning
confidence: 59%
“…The species, family and genera richness values of woody species (44 spp., 17 families and 26 genera) recorded in this study were higher than those reported from studies in Shorobe (41 spp., 15 families and 23 genera), Maun (area exclosure in Island Safari Lodge, 33 spp., 13 families and 20 genera) and Xobe (27 spp., 10 families and 24 genera) villages (Neelo et al, 2013;Neelo et al, 2015) as well as in an area exclosure of more than 10 years (32 spp., 12 familes and 19 genera) and open area adjacent the area exclosure (24 spp., 10 familes and 15 genera) in Maun (Teketay et al, 2016) in northern Botswana, and in Shekole (18 spp.) and Guba (23 spp.)…”
Section: Discussionmentioning
confidence: 99%
“…A threshold of H' = 2 has been mentioned as the minimum value above which an ecosystem can be regarded as medium to high diversity . The mean Shannon diversity index found in the Mopane woodlands of the study area was relatively low compared to similar habitats in northern Botswana; this is attributed to anthropogenic disturbance, suggesting that non-protected woodlands are negatively impacted by human activity, with a direct eff ect on the composition and diversity of species (Teketay et al, 2018). Within the study area we found H' values below 1; this may not only be related to the minimum number of plots surveyed, but also to the monodominance of single tree species such as Baikiaea plurijuga-Baphia massaiensisTerminalia sericea.…”
Section: Diversity Of the Woodlands Of Huíla Provincementioning
confidence: 99%